Determination of cholesterol turnover rate by a one-and two-pool kinetic analysis - Ginter, Emil; Ramacsay, L (Physiologia bohemoslovaca, 1977)
The cholesterol turnover rate in rabbits with alimentary cholesterol atherosclerosis and in guinea-pigs with chronic vitamin C deficiency was studied by a one- and two-pool kinetic analysis. The one-pool analysis yielded exaggeraged values for the turnover rate, but the turnover rate differences between the control and experimental groups in the one- and the two-pool analysis were very similar. One-pool analysis can be used in initial studies to obtain preliminary data on the effect of nutritional, pharmacological and other factors on cholesterol turnover rate.
Keywords: nedostatek vitaminu C; Rats; Diet, Atherogenic; Arteriosclerosis; křečci praví; radioizotopy uhlíku; Guinea Pigs; cholesterol dietní; dieta aterogenní; arterioskleróza; Mice; Cholesterol; krysa rodu Rattus; morčata; cholesterol; Ascorbic Acid Deficiency; zvířata; králíci; Rabbits; myši; Cricetinae; Carbon Radioisotopes; Cholesterol, Dietary; Animals